Eco-physiological response mechanism of Tamarix chinensis to soil water changes in coastal wetlands of the Yellow River Delta - Mao, Peili; Lin, Qingzhi; Pang, Yuanxiang; Wang, Kexin; Ni, Ruiqiang; Han, Xin; Cao, Banghua (Frontiers in Marine Science, 2023)
Elucidating the effect of soil moisture on the adaptation of dominant plants in coastal wetlands is important for predicting the evolution of vegetation in the region. In this paper, Tamarix chinensis, a dominant species in the Yellow River Delta, was used as the object to study the changes of its growth and physiological parameters with increasing soil salinity under different moisture conditions (normal watering, persistent drought and persistent waterlogging). Different salt stress (2‰, 5‰, 8‰, 12‰, 16‰, and 20‰) using pot experiments was also used to reveal the mechanism of soil moisture on its salt tolerance. The results showed that the relative growth rate between 5‰-8‰ soil salinity was the largest, and growth was significantly inhibited above 20‰. Among different moisture conditions, the difference in relative growth rate under normal watering and persistent drought were nonsignificant, while both were significantly lower than those under persistent waterlogging. With increasing soil salinity, relative water content and total chlorophyll content significantly decreased, and cell membrane permeability (malondialdehyde), sodium ion, osmoregulatory substances (proline, soluble protein), and protective enzyme activity (SOD) significantly increased, while changes in non-structural carbohydrates (NSC) were not significant. Compared with normal watering and persistent waterlogging, persistent drought had the lowest leaf relative water content, total chlorophyll content, and sodium ions, and the highest cell membrane permeability, osmoregulatory substances and protective enzyme activity. With increasing treatment time, the relative leaf water content and total chlorophyll content significantly decreased, and cell membrane permeability, osmoregulatory substances and protective enzyme activity increased more significantly than normal watering and persistent waterlogging. NSC increased under normal watering and persistent waterlogging, while significantly decreased under persistent drought. Correlation analysis showed that the relationships between sodium ions, total chlorophyll content and malondialdehyde were various under different moisture conditions. Under persistent drough, malondialdehyde was significantly positively correlated with relative conductivity, superoxide dismutase, proline, soluble protein and soluble sugar. Total chlorophyll content was the key indicator reflecting the salt and waterlogging tolerance of T. chinensis under normal watering and persistent waterlogging, while cell membrane damage was under persistent drought. In summary, T. chinensis has strong salt and waterlogging tolerance, but persistent drought with salt stress can have serious impacts on its growth and survival.